Produksi Program Jurnal 9 Pada TV9 Perspektif Media Islam - Nur Alfiana; Lukman Hakim (Journal of Islamic Civilization, 2019)
This research aims to describe the production process of journal 9 program on TV9 in the perspective of Islamic media. The production of journal 9 programs on TV9 in the perspective of Islamic media carries the principle of "Journalism Maslahat" based on Islamic journalistic ethics code including honesty, re-checking the news, the news delivered is effective and efficient news, becoming a disciplined and responsible journalist according with the religion of Islam. The management of the journal 9 production program on TV9 Nusantara is carried out through five elements namely production materials, production facilities, production costs, production implementing organizations, and stages of production implementation. Production Stage in the TV 9 Nusantara 9 Journal program which consists of the pre-production stage, the production stage (implementation), and the post-production stage (completion / editing and screening). The problems faced by TV9 in the production program are that broadcast production equipment is still not standard, production costs are still high, viewers' tastes in local programs are still not strong compared to National TV